DETERMINANTS OF STUNTING: A SYSTEMATIC REVIEW - Fidyah Aminin; Melly Damayanti; Nurul Aini Suria Saputri; Darwitri Darwitri (International Journal of Social Science, 2022)
One of the sustainable development goals (SDGs) is to end all forms of malnutrition by 2030. In 2015, undernutrition or stunting was considered to be an underlying contributing factor in about 45% of the 5.9 million children who died under the age of five. Referring to the impact it is important to know the factors that cause stunting. This study aims to determine the determinants of stunting. This study uses a Systematic Literature Study design from several selected materials using the PRISMA protocol method. The 14 study materials taken were obtained from 5 publications from PubMed, and 9 publications from Google Scholar. Based on identification results and 14 articles can be concluded that determinant factors of stunting consistently are economic social status (family income), infectious disease, mother's education, exclusive breastfeeding, low birth weight baby, premature birthing, inclusive mother's milk, birthing length, macro and micro deficiency, water dan circle sanitation, community, and social factors also significantly influence the stunting. It is hoped that there will be a government program that can support stunting prevention by considering the determinant of stunting